Partisipasi Masyarakat Dalam Program Pokok Pembinaan Kesejahteraan Keluarga Di Desa Bonerate Kabupaten Kepulauan Selayar (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
This study purposed to find out how community participation in the main program of family welfare development in Bonerate Village, Selayar Islands Regency. This study  used qualitative method. This study had 8  informants by using observation techniques, in-depth interviews and documentation. While the data analysis used  data reduction, data presentation, verification and conclusion. The results of this study showed that community participation in the main PKK program was quite well, due to community had awareness to participate  in activities that hold by the PKK activator team in Bonerate Village. In addition, community participation in the main PKK program could be seen in the form of community self-help both in terms of personnel and material. The problem was the  community had a low education in Bonerate Village. It was recommended that the participation of the Bonerate Village community in the PKK program needed to be increased again and the PKK Executing Team as the executor of the tasks in the Bonerate Village should optimize to involve  the community in various activities.